2013
DOI: 10.1016/j.brainres.2013.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Central 5-alpha reduction of testosterone is required for testosterone's inhibition of the hypothalamo-pituitary–adrenal axis response to restraint stress in adult male rats

Abstract: In rodents, the hypothalamo-pituitary-adrenal (HPA) axis is controlled by a precise regulatory mechanism that is influenced by circulating gonadal and adrenal hormones. In males, gonadectomy increases the adrenocorticotropic hormone (ACTH) and corticosterone (CORT) response to stressors, and androgen replacement returns the response to that of the intact male. Testosterone (T) actions in regulating HPA activity may be through aromatization to estradiol, or by 5α-reduction to the more potent androgen, dihydrote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…Indeed, during development, 5α-Rs participates in the generation of T-induced sex differences in the brain by the generation of 5α-DHT [45]. In the adult brain, 5α-Rs may mediate some of the rewarding effects of androgens [46] and is required for the inhibition exerted by T on the response of the hypothalamo-pituitary-axis to stress [47].…”
Section: Functions Of 5α-rs In the Central Nervous Systemmentioning
confidence: 99%
“…Indeed, during development, 5α-Rs participates in the generation of T-induced sex differences in the brain by the generation of 5α-DHT [45]. In the adult brain, 5α-Rs may mediate some of the rewarding effects of androgens [46] and is required for the inhibition exerted by T on the response of the hypothalamo-pituitary-axis to stress [47].…”
Section: Functions Of 5α-rs In the Central Nervous Systemmentioning
confidence: 99%
“…Indeed, to our knowledge, the effects of finasteride have so far generally been explored after the administration of very high doses [2,8,9,10,11,12,13,14,15,16,17,18]. We demonstrated that, in agreement with the well-known effect of finasteride in the prostate [35], a significant decrease in its relative weight was observed at the end of the subchronic treatment with the drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite of the wide therapeutic use of this inhibitor (e.g., human benign prostatic hyperplasia and androgenic alopecia), the effects of finasteride per se in the nervous system have been poorly explored. The effects of short exposures (i.e., a few days) to high doses (i.e., 50 mg/kg) of finasteride have been assessed in experimental models [2,8,9,10,11,12,13,14,15,16,17,18]. However, the effects of subchronic treatments with finasteride at low doses, more similar to those used in clinical practice, and the consequences of its withdrawal have yet to be clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic treatment of adrenalectomized rats with allopregnanolone indeed reduced expression of corticotropin-releasing hormone (CRH) within the hypothalamic periventricular nuclei. On the other hand, treatment of rats with the the 5α-reductase inhibitor finasteride increased their ACTH and corticosterone responses to acute stress [118,119]. Allopregnanolone and THDOC may thus be considered 22 as endogenous stress-protective hormones.…”
Section: Changes In Brain Steroid Levels In Response To Stressmentioning
confidence: 93%